2011
DOI: 10.4049/jimmunol.1003487
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 Shifts the Balance from Osteoclast to Alternatively Activated Macrophage Differentiation and Protects from TNF-α–Mediated Bone Loss

Abstract: IL-33 is a new member of the IL-1 family, which plays a crucial role in inflammatory response, enhancing the differentiation of dendritic cells and alternatively activated macrophages (AAM). Based on the evidence of IL-33 expression in bone, we hypothesized that IL-33 may shift the balance from osteoclast to AAM differentiation and protect from inflammatory bone loss. Using transgenic mice overexpressing human TNF, which develop spontaneous joint inflammation and cartilage destruction, we show that administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
98
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 46 publications
(47 reference statements)
14
98
1
1
Order By: Relevance
“…Consistent with previous reports (14,25,27,28), the addition of rmIL-33 to BMG cultures indeed induced production of G-CSF, but also of GM-CSF (D. Talabot-Ayer, C. Gabay, and G. Palmer, unpublished observations) and led to the emergence of a population of macrophage-like cells, contrasting with the preferential neutrophil expansion observed in CMV/IL33 mice in vivo. It is conceivable that IL-33 acts as a general activator of myelopoiesis, by directly or indirectly enhancing the proliferation of myeloid precursors, but that the final polarity of cell differentiation directing engagement into the neutrophil, macrophage, or eosinophil lineages in vivo will be influenced by the local and systemic contexts and cytokine milieu.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous reports (14,25,27,28), the addition of rmIL-33 to BMG cultures indeed induced production of G-CSF, but also of GM-CSF (D. Talabot-Ayer, C. Gabay, and G. Palmer, unpublished observations) and led to the emergence of a population of macrophage-like cells, contrasting with the preferential neutrophil expansion observed in CMV/IL33 mice in vivo. It is conceivable that IL-33 acts as a general activator of myelopoiesis, by directly or indirectly enhancing the proliferation of myeloid precursors, but that the final polarity of cell differentiation directing engagement into the neutrophil, macrophage, or eosinophil lineages in vivo will be influenced by the local and systemic contexts and cytokine milieu.…”
Section: Discussionsupporting
confidence: 91%
“…It is conceivable that IL-33 acts as a general activator of myelopoiesis, by directly or indirectly enhancing the proliferation of myeloid precursors, but that the final polarity of cell differentiation directing engagement into the neutrophil, macrophage, or eosinophil lineages in vivo will be influenced by the local and systemic contexts and cytokine milieu. This idea is further supported by published data documenting highly diverse effects of IL-33 on myeloid cell differentiation in BM cultures, according to the culture conditions used (14,15,(25)(26)(27)(28)(29)53).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These two members of the IL-17 family of cytokines have pro-inflammatory functions in a variety of animal models of inflammatory disease [41]. There actual role in human inflammatory disease remains to be defined, and so far, only preliminary evidence for an anti-inflammatory effect of specific inhibitors of IL-17 exists for disease such as rheumatoid arthritis.…”
Section: Il-17a and Il-17fmentioning
confidence: 99%
“…In CVB3 infection, the resistance of female mice to myocarditis is associated with the induction of type II cytokines and alternatively activated macrophages (M2) (7). We have previously reported that the recently discovered cytokine, IL-33, is a potent inducer of type II cytokines and M2 (8,9). We therefore investigated the role of IL-33 in CVB5-induced pancreatitis.…”
mentioning
confidence: 99%